Constant Curvature Translation Surfaces in Galilean 3-Space - Aydin, Muhittin Evren; Kulahci, Mihriban Alyamac; Ogrenmis, Alper Osman (Int Electronic Journal Geometry, 2019)
There are five different types of translation surfaces in a Galilean 3-space based upon planarity of generating curves and absolute figure. We obtain these surfaces with arbitrary constant Gaussian and mean curvature, except the type that both of generating curves are non-planar.
Keywords: Galilean space; translation surface; Gaussian curvature; mean curvature